Policing COVID-19 physical distancing measures: managing defiance and fostering compliance among individuals least likely to comply - McCarthy, Molly (Policing and society, 2021)
Physical distancing measures have become the first line of defence for slowing COVID-19 virus transmission. However, studies have demonstrated that compliance with physical distancing restrictions has not been uniform. Police have also encountered widespread resentment of the restrictions, defiance, and people purposefully flouting restrictions. In this study, we examined factors associated with compliance with COVID-19 restrictions among those who held defiant attitudes toward police during the early stages of the pandemic in Australia. The study draws on survey data collected from 1595 Australians during the initial lockdown period in Australia. Regression analysis was applied to determine if two forms of defiance toward police (resistance and disengagement) were associated with reduced compliance with restrictions while controlling for other known correlates of compliance. We also identified factors that were associated with compliance among highly resistant and disengaged individuals. Findings indicate that defiant individuals were significantly less likely to comply with physical distancing restrictions. Among highly resistant and disengaged individuals, recent police-initiated encounters that were deemed to be procedurally unjust were also associated with reduced compliance. In addition, highly disengaged individuals were less likely to comply if they were concerned about ongoing loss of freedoms post-COVID-19. The implications of the findings for defiance and compliance research, as well as for COVID-19 policing strategies, are discussed.